2022
DOI: 10.1097/j.pbj.0000000000000188
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of pathological conditions through electronic nose analysis of urine samples: a systematic review and meta-analysis

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…We acknowledge that by including various types of tumors or nonneoplastic diseases, and different biological media (e.g., urine, saliva, breath, blood, tumor specimen), more comprehensive pooled findings could potentially be obtained. Yet, it is crucial to say that combining such diverse diseases with unique biological characteristics and odor signatures might introduce biases and hinder accurate interpretations, as also demonstrated in studies by Scheepers et al [49], Afonso et al [114], and other authors. Considering the assumptions above, our study has shown an I 2 of 57% for sensitivity and 66% for specificity, indicating a "significant" degree of heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…We acknowledge that by including various types of tumors or nonneoplastic diseases, and different biological media (e.g., urine, saliva, breath, blood, tumor specimen), more comprehensive pooled findings could potentially be obtained. Yet, it is crucial to say that combining such diverse diseases with unique biological characteristics and odor signatures might introduce biases and hinder accurate interpretations, as also demonstrated in studies by Scheepers et al [49], Afonso et al [114], and other authors. Considering the assumptions above, our study has shown an I 2 of 57% for sensitivity and 66% for specificity, indicating a "significant" degree of heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a series of studies have proposed novel methods, such as the diagnosis of BAD through the detection of volatile organic compounds (VOCs) produced by gut microbiota metabolism. By analyzing the VOCs, the status of the gut microbiota can be inferred, allowing for the assessment of bile acid metabolism and subsequent diagnosis of BAD [73][74][75][76]. By conducting bacteriome analysis and volatile gas testing on both BAD patients and healthy individuals, it is possible to identify distinguishing features.…”
Section: Detecting Intestinal Microbiota and Its Metabolitesmentioning
confidence: 99%